Comparative evaluation of airports productivity towards tourism development - Dimitrios J. Dimitriou (Taylor & Francis Group, 2018)
The link between tourism and aviation is at the top of the agenda of many academic institutes, professional associations and regulatory authorities, mainly, because of the both industries high competitive business environment resulting demand volatility and business unpredictability. Airports serving tourist destinations are essential counterpart of the tourist demand supply chain and their productivity impact essential the mobility cost, the connectivity and the region’s attractiveness. This paper deals with the airport productivity assessment towards regional development (RD) for regions heavily dependent on tourism. The methodological approach promotes two essential steps: (a) the introduction of a set of key performance indicators (KPI) providing essential messages towards airport’s contribution in tourist regions and (b) a performance benchmarking for a group of airports with similar characteristics serving high demanded tourist destinations. The assessment methodology is based on a multi-objective unweighted analysis, introducing six KPIs to provide messages towards airport productivity contribution in RD, in the scale of strategic planning. The assessment framework uses a sample of seven islands constitute very attractive European tourist destinations for summer holidays and the assessment outputs provide key messages to planners, managers and decision-makers towards aviation and tourism interaction.